My Nature Land - Dashdorj Natsagdorj (Symphony in the Flint Hills, 2015)
A poem by Dashdorj Natsagdorj on his love and passion for his native land: Mongolia.
Keywords: mountains; nature; native; landscape; great; seasons; ancient; love; adoration; home; peace; poem; poet